Defisiensi Vitamin B1 dan B6, Asupan Gizi, serta Kadar IGF-1 sebagai Faktor Risiko Stunting pada Anak Usia 24-60 Bulan: Vitamin B1 and B6 Deficiency, Nutrient Intake, and IGF-1 Levels as Risk Factors for Stunting in Children Aged 24-60 Months - Putriatri Krimasusini Senudin; Irwanto Irwanto; Nur Aisiyah Widjaja; Sulistiawati Sulistiawati (Amerta Nutrition, 2025)
Background: Stunted growth in height, caused by chronic malnutrition, is most prevalent among children in Indonesia, with the highest rates observed in the province of East Nusa Tenggara. The balance of macronutrients and micronutrients plays a crucial role in regulating IGF-1, which is essential for height growth. Objectives: This study aims to analyze the differences in macronutrient and micronutrient levels, as well as IGF-1, between stunted and normal children, and to examine their impact on the incidence of stunting. Methods: The research was conducted in Langke Rembong District, Manggarai Regency, from October to December 2024. This case-control study involved 80 respondents, comprising 40 children in the stunted group and 40 in the normal group. Nutritional intake was assessed using a 24-hour food recall and analyzed with the Nutrisurvey 2007 application, with results compared to the Recommended Dietary Allowances (RDA). IGF-1 levels were measured from serum using the ELISA test. Univariate statistical tests and the Mann-Whitney U test were used to analyze the differences in macro and micronutrient as well as IGF-1 between the two groups and their impact on the incidence of stunting. Results: There were significant differences in the intake of macronutrients, including carbohydrates, protein, and fat (p-value<0.001); micronutrients, including vitamin A, B1, B2, B6, magnesium, iron, zinc, and phosphorus (p-value<0.001), as well as vitamin C (p-value=0.018) and calcium (p-value=0.007); and in IGF-1 levels (p-value=0.030) between stunted and normal children. Children aged 24-60 months had a stunting risk of 38.07 and 25.38 when deficient in vitamin B1 and vitamin B6, respectively. Conclusions: To combat and prevent stunting, it is crucial to monitor micronutrient intake, particularly vitamins B1 and B6.